Craft Design Collaboration: Exploring a Locally Inspired Motif for The Tasikmalaya Embroidery - Martono, John; Puspita, Eka Arifianty; Batik, Iradaniatri Rejeky (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Traditional crafts are important for exposing regional identity. Lack of originality in the way crafts represent regional characteristics will expose them to imitation, trap them in a competitive market, and eventually threaten their sustainability in a creative economy. Consumer trends are certainly important for traditional craft growth, but so is the intangible dimension, which is typically shaped by economic, cultural, and technological factors. The potential economic value of culture-based enterprises is revealed by attempts to commercialize the distinctive intangible creativity, just like in creative industries, by highlighting the distinctiveness of locale. The purpose of this study was to explore the creative potentials that show the distinctiveness of the local Tasikmalayan embroidery craft. Since designers are taught to consider collective factors while making design decisions, design intervention is required for this endeavor. Thus, Tung's craft and design collaboration model will be used for the research, which encourages Tasikmalayan embroidery designers and craftsmen to work together from the beginning to the end. A team of designers will work together with Gallery Kiwari, a Tasikmalayan embroidery craft MSME, to create new embroidery craft motifs that promote local identity. Although the research yielded two prototypes that reflected the location and the character of the artisans, the collaborative method also gave the craftsmen opportunities to learn and create designs that supported local richness. Through the experience, it is anticipated that the craftsmen will be able to develop their future original ideas and elevate the variety of embroidery crafts that symbolize the local value of Tasikmalaya.